Construction of a Novel circRNA/miRNA/mRNA Regulatory Network to Explore the Potential Pathogenesis of Wilson’s Disease - Wei, Taohua; Qian, Nannan; Yang, Wenming; Yang, Yue; Liu, Jie; Hao, Wenjie; Cheng, Ting; Yang, Ran; Dong, Wei; Yang, Yulong (Frontiers in Pharmacology, 2022)
Studies show that non-coding RNAs, especially microRNAs (miRNAs) and circular RNAs (circRNAs), and protein-coding genes are involved in the pathophysiology of multi-organ damage caused by Wilson’s disease (WD). However, circRNA expression profiles and their role in initiation and progression of WD kidney injury remain largely unclear at present. Here, we explored potential critical protein-coding genes, miRNAs, and circRNAs, as well as identify competitive endogenous RNAs (ceRNAs) in a WD mouse model by high-throughput sequencing. We investigated the expression profiles of circRNAs, miRNAs, and protein-coding genes, and identified 32 DEcircRs, 45 DEmiRs, and 1623 DEPs. Identified DEcircRs, DEmiRs, and DEPs were used to construct a ceRNA network, which consisted of 15 DEcircRNAs (four upregulated and 11 downregulated), 18 DEmiRNAs (14 upregulated and four downregulated), and 352 DEmRNAs (205 upregulated and 147 downregulated). Further experiments proved that mmu_circ_0001333 and mmu_circ_0000355 acted as sponges of miR-92b-5p, miR-107-3p, and miR-187-3p to regulate the expression of genes including Smad9, Mapk10, and Aldh3a2, which may participate in WD-related kidney injury. Taken together, this study identified the circRNA/miRNA/mRNA network involved in kidney failure in WD, which may serve as a potential biomarker for the pathogenesis of WD.